Actors and dynamics in the Syrian conflict's middle phase between contentious politics, militarization and regime resilience - Gani, Jasmine; Hinnebusch, Raymond 1946- (Routledge/St. Andrews Syrian studies, 2022)
"This volume covers the "middle" time period of the Syrian uprising, roughly from 2012 when Syria's peaceful protest began to mutate into a violent insurgency and civil war until roughly 2018 when the conflict took on features of a "frozen conflict." The middle period was important as one of key junctures or turning points when the struggle could have reached rather different outcomes. Non-violent protest failed to drive democratization and turned into violent insurrection but revolution from below also failed as did regime counter-insurgency, leaving protracted civil war the default outcome. Second, the consequences of civil war became evident with five themes: failing statehood coexisted with regime resilience; rebel governance emerged as a viable challenge to the regime; social forces were sharply polarized; external actors exacerbated internal divisions; a predatory war economy emerged; and intense violence led to massive displacement of the population. Taking an innovative and interdisciplinary approach that seeks to capture the full complexity of the phenomenon, this book contributes significantly to our understanding of the Syrian conflict, therefore it will be of interest to academics, students, journalists and policy-makers interested in the Syrian civil war"--